On-column refolding of recombinant fungal endoglucanase I - Aizat Jamaluddin, Mohd Jamil; Mohd. Salleh, Hamzah (2011)
Endoglucanase is an industrially important enzyme involved in degradation of cellulosic materials into constitutive monomers synergistically with other cellulase enzymes. In this study, overexpression of (His)6-tagged endoglucanase I from Fusarium oxysporum sp. in E. coli BL21(DE3) resulted to high tendency of endoglucanase I in the form of inactive inclusion bodies when the host cells were cultured between 25-37°C and induced by 0.05-0.20 mM (final concentration) IPTG. A simple and time-efficient on-column refolding scheme using IMAC aided by AKTA purifier, an automated fast protein liquid chromatography (FPLC) system afforded highly purified refolded recombinant endoglucanase I that was active in carboxymethyl cellulose (CMC) assay. The on-column refolding scheme is reliable and can be applied for efficient and robust method for lab-scale production of recombinant endoglucanase I.